Oligomerization is involved in pore formation by Bordetella adenylate cyclase toxin - Vojtova-Vodolanova, Jana; Basler, Marek; Osicka, Radim; Knapp, Oliver; Maier, Elke; Cerny, Jan; Benada, Oldrich; Benz, Roland; Sebo, Peter (FASEB journal, 2009)
The Bordetella adenylate cyclase-hemolysin (CyaA, ACT, or AC-Hly) is a multifunctional toxin. Simultaneously with promoting calcium ion entry, CyaA delivers into host cells an adenylate cyclase enzyme (AC) and permeabilizes cell membrane by forming small cation-selective pores. Indirect evidence suggested that these two activities were accomplished by different membrane-inserted CyaA conformers, one acting as an AC-delivering monomer and the other as an uncharacterized pore-forming oligomer. We tested this model by directly detecting toxin oligomers in cell membrane and by assessing oligomerization of specific mutants with altered pore-forming properties. CyaA oligomers were revealed in sheep erythrocyte membranes by immunogold labeling and directly demonstrated by pulldown of membrane-inserted CyaA together with biotinylated CyaA-AC(-) toxoid. Membrane oligomers of CyaA could also be resolved by nondenaturing electrophoresis of mild detergent extracts of erythrocytes. Furthermore, CyaA mutants exhibiting enhanced (E581K) or reduced (E570K+E581P) specific hemolytic and pore-forming activity were found to exhibit also a correspondingly enhanced or reduced propensity to form oligomers in erythrocyte membranes. On the other hand, processed CyaA, with the AC domain cleaved off by erythrocyte proteases, was detected only in a monomeric form excluded from the oligomers of unprocessed CyaA. These results provide the first direct evidence that oligomerization is involved in formation of CyaA pores in target membranes and that translocation of the AC domain across cell membrane may be accomplished by monomeric CyaA.
Keywords: hemolýza; Hemolysis; Mutation, Missense; Endocytosis; multimerizace proteinu; missense mutace; Adenylate Cyclase Toxin; Bordetella; ovce; Sheep; Cell Membrane Permeability; endocytóza; permeabilita buněčné membrány; Animals; zvířata; erytrocyty; Erythrocytes; adenylátcyklasový toxin; Protein Multimerization